Difference between revisions of "2016 APMO Problems/Problem 5"
(→Solution) |
(→Solution) |
||
Line 28: | Line 28: | ||
This gives that <math>\text{Im}(f) \in \left(\frac{f(2x)}{2},\infty\right)</math>. Putting <math>x=\frac{1}{2}</math>, we get <math>\text{Im}(f) \in \left(\frac{1}{2},\infty\right)</math>. By induction, surjectivity is proved as <math>\lim_{m \to \infty}\frac{1}{2^m}=0</math> and we are essentially done. <math>\square</math> | This gives that <math>\text{Im}(f) \in \left(\frac{f(2x)}{2},\infty\right)</math>. Putting <math>x=\frac{1}{2}</math>, we get <math>\text{Im}(f) \in \left(\frac{1}{2},\infty\right)</math>. By induction, surjectivity is proved as <math>\lim_{m \to \infty}\frac{1}{2^m}=0</math> and we are essentially done. <math>\square</math> | ||
− | Now, we have claim that if <math>a+b=c+d</math> for some <math>a,b,c,d \in \mathbb{R}^+</math>, then <math>f(a)+f(b)=f(c)+f(d)</math>. This can be achieved by putting <math>a=xf(z)+y</math>, | + | Now, we have claim that if <math>a+b=c+d</math> for some <math>a,b,c,d \in \mathbb{R}^+</math>, then <math>f(a)+f(b)=f(c)+f(d)</math>. This can be achieved by putting <math>a=xf(z)+y</math>, <math>b=yf(z)+x</math>, <math>c=x'f(z)+y'</math> and <math>d=y'f(z)+x'</math>. Let us calculate <math>f(a)+f(b)</math> now. |
+ | e | ||
+ | <cmath>f(a)+f(b)=(z+1)f(x+y)=(z+1)f\left(\frac{a+b}{f(z)+1}\right)=(z+1)f\left(\frac{a'+b'}{f(z)+1}\right)=(z+1)f(x'+y')=f(a')+f(b').</cmath> |
Revision as of 03:28, 14 July 2021
Problem
Find all functions such that
for all positive real numbers
.
Solution
We claim that is the only solution. It is easy to check that it works. Now, we will break things down in several claims. Let
be the assertion to the Functional Equation.
Claim 1: is injective.
Proof: Assume for some
. Now, from
and
we have:
Now comparing, we have as desired.
This gives us the power to compute . From
we get
and injectivity gives
. Showing that
is unbounded above is also easy as we can fix
and let
blow up to
in the original Functional equation..
Claim 2: is surjective.
Proof: gives
This gives that . Putting
, we get
. By induction, surjectivity is proved as
and we are essentially done.
Now, we have claim that if for some
, then
. This can be achieved by putting
,
,
and
. Let us calculate
now.
e